Learning for leadership : a facilitative approach for training leaders - Hellman, Yael (ASTD Press, 2014)
This book builds on foundational learning and development concepts and practices to help trainers and facilitators develop programs that meet the challenges of teaching leadership and turn learners into leaders. Yael Hellman illustrates how a truly "facilitative" classroom is structured, and she shows why it is the best environment to learn leadership skills. The author does so through the lens of group dynamics and her own experience facilitating leadership courses for the Los Angeles Police Department. The facilitative approach invites learners to practice leadership by being accountable for reaching learning objectives, taking initiative to solve problems, and nurturing their own ideas rather than leaning on authority. This book includes everything you need to develop a facilitative leadership development course, including: icebreakers or warm-ups to focus learners on the session's agenda; interactive instruction models to help them master content; ideas for group work, including collective projects; experiential exercises or games and joint activities that immediately apply new material; wrap-ups to summarize one session and link it to an upcoming one. Facilitation integrates techniques from many adult learning approaches to produce creative, transformative, practical learning and leaders who are prepared to lead."--